Integrasi Sistem Informasi Bisnis Dengan Teknologi Machine Learning - Indah Riski Panjaitan; Muhammad Irwan Padli Nasution (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2024)
This article discusses the integration of business information systems with machine learning technology to enhance decision-making efficiency and accuracy. The objective of this research is to implement machine learning algorithms into business information systems to automatically process and analyze data, predict business trends, and provide more intelligent recommendations. The methods involve collecting historical data from business information systems, applying machine learning algorithms such as regression, classification, or clustering, and integrating the analysis results into the BI platform. The outcome is an enhanced capability of business information systems to optimize supply chains, identify consumer behavior patterns, and optimize marketing strategies based on more accurate predictions. Integrating machine learning technology with business information systems proves to be an effective strategy for improving a company's competitiveness in the current digital era.